Persistence and change of regional industrial activities: The impact of diversification in the German machine tool industry - Dirk Fornahl; Christina Guenther (Max Planck Institute of Economics, 2008)
The paper Investigates stability and change of regional economic activities in the long-run. As the unit of analysis we selected the machine tool industry in West Germany for the years 1953 to 2002. We spot a strong variance in the activities between the different regions. These differences are relatively stable over time and the regional activities are rather path-dependent. Nevertheless, the paper also identifies changes in the level of activities. As the main driving factors for these changes we examine the effect of regional diversification strategies. We find that those regions pursuing a general diversification strategy have a higher likelihood to grow than regions which are specialising. Furthermore, diversification into totally new technological and product fields is only beneficial under specific circumstances based on technological and market developments. Hence, in most cases a broad diversification is superior to one focusing on new state-of-the-art technological fields.
Keywords: L61; O1; O18; R11; R12; 330; Geographic concentration; specialisation indices; machine tool industry; path-dependencies; agglomeration economies